Synthesis of obscuraminol A using an organocatalyzed enantioselective Henry reaction. Issue 41 (13th October 2016) - Filippova, Liudmila; Antonsen, Simen; Stenstrøm, Yngve; Hansen, Trond Vidar
Abstract: The first synthesis of the polyunsaturated amino alcohol natural product obscuraminol A is reported. This stereoselective synthesis was based on an anti - and enantioselective organocatalyzed Henry reaction followed by a chemoselective SmI2 -mediated reduction that affected only the nitro-group of the Henry product. These efforts yielded obscuraminol A where the configuration of the all- Z skipped double bonds was conserved from the starting material, i.e . the ethyl ester of (all- Z )-eicosa-5, 8, 11, 14, 17-pentaenoic acid. Our synthesis confirmed the reported structure of obscuraminol A. Graphical abstract: